Implementation of Religious Activities in Increasing the Spiritual Intelligence of Students - Deli Musdalifa; Fatimah Saguni; Gusnarib Gusnarib (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2020)
The aim of this paper is to discusses the practice of cousin marriage in the community of Kalola Village, Pasangkayu Regency, West Sulawesi. This study uses qualitative methods and data was gathered through observation, in-depth interviews, and written material. Data analysis was analyzed using grounded theory approach. The results show that the religious activities in MAN insan Cendekia Palu City were congregational prayer activities, qiroatul quran, tahfiz Alquran, Qiro'ah qabla naum, Ratibul haddal / barzanji, polar Qiraatul / book study, three-language cult. The religious activities are carried out outside school hours, from 05.00-05.30 and continued at 18.30-19.15 and then continued again at 21.45-22.00, the activities are carried out at the mosque for male students and in the dormitory for girls, for brazanji and evening prayers and Isha all students carry out in the mushollah. Togetherness activities have six coaches, namely 3 male dormitory coaches and 3 female coaches, the friendship activity supervisor is a competent coach with activities carried out by the implementation process itself carried out by providing training, coaching and habituation so that the expected goals can be achieved.